2010
DOI: 10.1111/j.1399-3062.2009.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower incidence of cytomegalovirus infection with everolimus versus mycophenolate mofetil inde novocardiac transplant recipients: a randomized, multicenter study

Abstract: Cytomegalovirus (CMV) is a major cause of infectious complications following cardiac transplantation, severely affecting short- and long-term outcomes. A 12-month, multicenter, randomized, open-label study in de novo cardiac transplant patients was undertaken to compare the efficacy, renal function, and safety of everolimus plus reduced cyclosporine versus mycophenolate mofetil (MMF) plus standard cyclosporine (ClinicalTrials.gov NCT00150046). CMV-specific data was prospectively collected on infections, labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 25 publications
3
32
1
1
Order By: Relevance
“…mTORi may present antiviral properties [82,83 && ,84] as reduction of cytomegalovirus (CMV) incidence with mTORi regimens was consistently reported, whatever the antiviral treatment used [85][86][87]. In fact, statistical significance was only reached for recipients with CMV-positive status before transplantation [88]; lower incidence of BK virus (BKV) infection has been inconsistently reported [66, 88,89].…”
Section: Beneficial Effects Of the Mechanistic Target Of Rapamycin Inmentioning
confidence: 99%
“…mTORi may present antiviral properties [82,83 && ,84] as reduction of cytomegalovirus (CMV) incidence with mTORi regimens was consistently reported, whatever the antiviral treatment used [85][86][87]. In fact, statistical significance was only reached for recipients with CMV-positive status before transplantation [88]; lower incidence of BK virus (BKV) infection has been inconsistently reported [66, 88,89].…”
Section: Beneficial Effects Of the Mechanistic Target Of Rapamycin Inmentioning
confidence: 99%
“…Several recent studies have reported that the immunosuppressive agents sirolimus (rapamycin) and its derivative everolimus are associated with a significantly reduced incidence of HCMV infections in both solid organ transplant recipients (64,93,196) and allogeneic hematopoietic stem cell recipients (145). A switch to sirolimus has also been reported to be associated with reduced viral loads in patients infected with GCV-resistant HCMV strains (160).…”
Section: Drugs Approved For Other Diseases or Conditionsmentioning
confidence: 99%
“…In vitro exposure of infected cells to rapamycin results in transient or incomplete inhibition of virus infection (55,105,117), but no specific antiviral target has been identified. It is assumed that there is an indirect effect through inhibition of host cell proliferation and signaling pathways (105,117,196). Drugs that have both immunosuppressive and anti-HCMV activity could be therapeutically advantageous in transplant recipients.…”
Section: Drugs Approved For Other Diseases or Conditionsmentioning
confidence: 99%
“…Third, everolimus interferes with the phosphatidylinositol 3-kinase pathway, a critical step for viral signaling and replication. There is convincing evidence indicating a reduced rate of cytomegalovirus (CMV) infection in everolimus-treated heart transplant recipients [1315]. Fourth, everolimus exhibits antiproliferative activity.…”
Section: Introductionmentioning
confidence: 99%